Marriage Agreement as an Effort to Realize a Sakinah Mawaddah Warahmah Family: Analysis Based on the Prophet's Hadith - Guspidawati, Lenny; Husti, Ilyas; Sarifandi, Suja'i (Jurnal El-Thawalib, 2025)
A marriage contract is an essential instrument for building a harmonious and just household, especially in modern society, which faces increasingly complex social, economic, and cultural dynamics. In Islamic tradition, the concept of agreement or conditions in marriage has been recognized through various hadiths of the Prophet, which emphasize the importance of fulfilling promises and the legality of conditions as long as they do not conflict with sharia. Therefore, this study aims to analyze the concept of a marriage contract for realizing a family of sakinah, mawaddah, and warahmah, based on the Prophet's hadith as the primary normative basis. This study is a qualitative, library-based study using a normative-theological approach. Data sources include primary sources, such as significant hadith collections such as Sunan Abu Dawud, Sunan Tirmidhi, and Musnad Ahmad, as well as secondary sources, including fiqh literature, academic journals, and related laws and regulations. Data collection techniques involved documentation and literature analysis, while data analysis used content analysis to interpret the textual and contextual meanings of relevant hadiths. The research results show that the Prophet's hadith strongly legitimizes a marriage contract, provided the stipulated conditions do not permit what is forbidden or prohibit what is permissible. This agreement can be a strategic tool for clarifying the rights and obligations of husband and wife, preventing conflict, and supporting the achievement of the goals of marriage characterized by tranquility, compassion, and mercy. Therefore, a marriage contract, from the perspective of the hadith, is not only valid under Islamic law but also a relevant mechanism for strengthening the unity of contemporary Muslim families.